Repair of Proximal Hamstring Tear Utilizing a Suture Bridge Knotless Construct. (3rd August 2020) - Sanderson, Brent; Stumetz, Kyle; Jazayeri, Reza
Abstract : Proximal hamstring tendon injuries occur frequently in the athletic population resulting in varying degrees of functional disability depending on severity of injury. The purpose of our case vignette is to describe a surgical technique and clinical outcome for open proximal hamstring tendon repair with a confirmed biomechanically sound construct. We also describe and summarize the current literature recommendations for proximal hamstring injuries. We present a case and surgical technique report on a 27-year-old male who suffered a proximal hamstring tendon rupture. Utilizing a double row all-knotless suture bridge construct with a total of four anchors and six suture limbs allowed for anatomic footprint coverage and strength. Two years of clinical follow-up was obtained evaluating hip and knee range of motion, strength, and functional ability. Our patient underwent uncomplicated open surgical repair and returned to all activity at four months following surgery. Range of motion and strength returned to preoperative levels at the four-month postoperative mark. The use of a reproducible double row all-knotless suture bridge technique provided adequate strength and stability in the setting of a proximal hamstring tendon rupture. Open and endoscopic surgical techniques performed acutely both show positive postoperative subjective outcomes as well as a high likelihood of returning to sport. Controversy remains present in regard to the repair technique as well as postoperative bracing and physical therapy recommendations.